2015
DOI: 10.1007/s11432-015-5459-7
|View full text |Cite
|
Sign up to set email alerts
|

RECTANGLE: a bit-slice lightweight block cipher suitable for multiple platforms

Abstract: In this paper, we propose a new lightweight block cipher named RECTANGLE. The main idea of the design of RECTANGLE is to allow lightweight and fast implementations using bit-slice techniques. RECTANGLE uses an SP-network. The substitution layer consists of 16 4 × 4 S-boxes in parallel. The permutation layer is composed of 3 rotations. As shown in this paper, RECTANGLE offers great performance in both hardware and software environment, which provides enough flexibility for different application scenario. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
186
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 29 publications
(31 reference statements)
4
186
0
Order By: Relevance
“…(11), the number of balanced bits increases in Eq. (10). In this way, upper bound of integral distinguisher can not be obtained if we do not consider other integral distinguisher than m-th order one.…”
Section: Problem Of Conventional Algorithmmentioning
confidence: 96%
See 2 more Smart Citations
“…(11), the number of balanced bits increases in Eq. (10). In this way, upper bound of integral distinguisher can not be obtained if we do not consider other integral distinguisher than m-th order one.…”
Section: Problem Of Conventional Algorithmmentioning
confidence: 96%
“…In the implementation of block ciphers in GPGPU, we consider three parameters needed for acceleration in Sec.5.1. In Sec.5.2, we execute computer experiment in HIGHT [3], LBlock [5], TWINE [8], PRESENT [1] and RECTANGLE [10] and show their execution times.…”
Section: Acceleration Of Computer Experiments By Gpgpumentioning
confidence: 99%
See 1 more Smart Citation
“…RECTANGLE [19] is a bit-slice ultra-lightweight block cipher suitable for multiple platforms which achieve very low area in hardware and also very competitive performance in software. RECTANGLE is SPN structure, the substitution layer (S-layer) consists of 16 4 bits S-boxes, the permutation layer (P-layer) is composed of 3 rotations.…”
Section: Rectanglementioning
confidence: 99%
“…We observed that 73% of all possible bijective 3 × 3 S-boxes contain differential factors. Moreover, 4 × 4 S-boxes of DES [28], GOST [39], LBLOCK [41], LED [18], LUFFA [12], NOEKEON [15], Piccolo [35], Present [11], RECTANGLE [42], SARMAL [40], SERPENT [1], spongent [10] and Twofish [33] contain differential factors.…”
Section: Introductionmentioning
confidence: 99%